2021
DOI: 10.4049/jimmunol.2001025
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Severe SARS-CoV-2 Infection in Humans Is Defined by a Shift in the Serum Lipidome, Resulting in Dysregulation of Eicosanoid Immune Mediators

Abstract: The COVID-19 pandemic has affected more than 20 million people worldwide, with mortality exceeding 800,000 patients. Risk factors associated with severe disease and mortality include advanced age, hypertension, diabetes, and obesity. Each of these risk factors pathologically disrupts the lipidome, including immunomodulatory eicosanoid and docosanoid lipid mediators (LMs). We hypothesized that dysregulation of LMs may be a defining feature of the severity of COVID-19. By examining LMs and polyunsaturated fatty … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
161
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 41 publications
11
161
1
Order By: Relevance
“…Given growing evidence suggesting that lipid metabolism plays a critical role in determining COVID-19 outcomes, we sought to identify molecular mechanisms that reconcile key lipidomic changes. Untargeted lipidomic analysis in this study, consistent with other reports, suggest that PLA 2 activation and mitochondrial dysfunction are central determinants of COVID-19 severity and mortality 14,15,22,23 . Specifically, significant elevations in lyso-PLs (PE, PS, but not PC) and increased linoleic and oleic acid levels are hallmarks of catalysis by a sPLA 2 isoform.…”
Section: Resultssupporting
confidence: 91%
“…Given growing evidence suggesting that lipid metabolism plays a critical role in determining COVID-19 outcomes, we sought to identify molecular mechanisms that reconcile key lipidomic changes. Untargeted lipidomic analysis in this study, consistent with other reports, suggest that PLA 2 activation and mitochondrial dysfunction are central determinants of COVID-19 severity and mortality 14,15,22,23 . Specifically, significant elevations in lyso-PLs (PE, PS, but not PC) and increased linoleic and oleic acid levels are hallmarks of catalysis by a sPLA 2 isoform.…”
Section: Resultssupporting
confidence: 91%
“…Among other lipid species, phosphatidylserines were cited as decreased metabolites in COVID-19 5,10,11,13 . Four previous studies reported reduced levels of PS in COVID-19 cases 5,11 , even when mild 10 , moderate and severe 13 cases were compared to controls, on both blood-derived samples 5,10,13 and naso-oropharyngeal swabs 11 , corroborating our findings. PS is a negatively-charged membrane phospholipid that may translocate from inner to outer cell membrane layer in early stages of viral infection 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study in which lipid mediators were analyzed from sera obtained from SARS-CoV-2-infected patients and healthy controls found that increased PUFA containing lipids were increased in infected patients, and this PUFA pattern was exacerbated with increasing COVID-19 disease severity. Moderate and severe disease was characterized by higher levels of 5-HETE and 12-HETE, suggesting that PUFA metabolites and, in particular, the 12-LOXs may play a paramount role in COVID-19 infection [ 136 ]. These data suggest a clear role in the systemic lipid biomolecule network in the pathogenesis of COVID-19.…”
Section: Role Of 12-lox In Covid-19mentioning
confidence: 99%